(untitled) (EU and comparative law issues and challenges series (ECLIC), 2019)
Current article takes a closer look at the dialogue between the Strasbourg and the Luxembourg courts on the interpretation of the ne bis in idem principle and analyses how it influenced the (non)acceptance of the possibility to conduct both, criminal and administrative penal proceedings, against the same person for the same acts. It starts with the pre-Zolotukhin jurisprudence of the European Court for Human Rights and analyses how the Luxembourg interpretation of Article 54 CISA had a major influence on the change in the way the Strasbourg court perceived the possibility to conduct both, criminal and administrative penal proceedings, against the same person for the same acts. It further explores how the Luxembourg court followed the way indicated by Zolotukhin and accepted the stance of the Strasbourg court on the possibility of duplication of criminal and administrative penal proceedings against the same person for the same acts under the ne bis in idem protection afforded to individuals by Article 50 of the Charter of Fundamental Rights of the European Union. Finally, it analyses whether the recent shift in the Strasbourg court’s jurisprudence, which was also followed by the Luxembourg court, means that the ne bis in idem principle in European criminal law has, on the question of the duplication of criminal and administrative penal proceedings, basically come to the positions which were dominant in the pre-Zolotukhin jurisprudence.